Osteomyelitis of the mandible in children—Clinical presentations and review of management - Ord, R.A.; El-Attar, A. (British journal of oral & maxillofacial surgery, 1987)
Four cases of osteomyelitis of the mandible in children are reported to illustrate the spectrum of presentation. A proliferative rather than a lytic bony response is usually seen due to attenuation of the causative organisms and the improved immunological status of children in Britain. The importance of penicillin-resistant organisms and anaerobes, early diagnosis by scintigraphy and the use of hyperbaric oxygen therapy are highlighted.